Z dziejów Polskiego Stronnictwa Ludowego w powiecie sieradzkim (1945–1947) - Olejnik, Leszek (Zeszyty Wiejskie, 2012)
In the article introduced selected problems of the functioning of an independent peasant movement in district Sieradz in the first years after the Second World War. After the creation of the Provisional Government of National Unity and after the return of former Prime Minister in Exile Stanisław Mikołajczyk to the country there are major changes in the peasant movement. Formed an independent Polish Peasants Party, which is popular opposition to strengthen their authority Communists. In province of Łódź the party formed in the autumn 1945. This happens through massive transformation of local organizations already existing Peasants Party (Stronnictwo Ludowe – SL) in the structure of the Polish Peasants Party (Polskie Stronnictwo Ludowe – PSL). Of the constitution – 17th November 1945 – for about half of next year PSL in district Sieradz developed fast. Since then, Communists authorities have intensified the fight against the party led by S. Mikołajczyk. Secessions were inspired in the ranks of PSL, eliminated the influence of this group in local power structures and above all, party activists were repressed in a wide range. Mass arrests were intended to intimidate that political environment. Consequently of such actions at the turn of 1946 and 1947 the activities of PSL froze. In March 1947 some members and activists of PSL in district Sieradz went to the pro-Communist SL. Spring 1947, inspired by The Provincial Board of PSL in Lodz, in district Sieradz have been made recovery attempts of indepentent PSL. Communist Security Apparatus prevented them effectively.